THE EFFECTIVENESS OF ISLAMIC RELIGIOUS EDUCATION IN THE FAMILY ON STUDENTS' RELIGIOUS ATTITUDES - Irfandi; Yasir Arafat; Zainul Hakim; Sudiyo; Nanang Lidwan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Islamic religious education is crucial for children because it provides a strong moral and ethical foundation for their lives. Islamic religious education can also help them understand moral values, such as honesty, patience, tolerance, and a sense of responsibility. This can shape a child's character, leading to individuals with noble character and respect for others. The role of the family in educating children is crucial because parents are their children's first teachers, teaching them about Islamic religious education. The effectiveness of Islamic religious education within the family on students' religious attitudes reflects their experience of religion, which concerns a person's inner life, as religious attitudes cannot be separated from their adherence to their own religion. Attitude formation and change are influenced by two factors: (1) Internal factors, namely the ability to select and analyze external influences, including interest and attention. Humans are essentially born with a natural state (innate religious potential), and only environmental factors (parents) influence the development of a child's religious innate nature. (2) External factors, namely factors external to the individual, namely environmental influences received. The external factor is that humans possess basic potential that can be developed as religious beings. This potential is generally referred to as a religious innate nature. The type of research used by the researcher is a survey and is a qualitative study. It explores field data using descriptive analysis methods. This aims to provide a quick and accurate picture of the effectiveness of Islamic religious education in families on students' religious attitudes. The research method used is qualitative. The data collection techniques used in this study include: observation, interviews, and documentation.